Survey of the knowledge levels for ıntramuscular ınjectıon applıcatıon of nursıng students - Karaahmetoğlu, Gülşen Ulaş (LookUs Bilisim A.S., 2019)
INTRODUCTION: Study was conducted as a descriptive study to determine the level of knowledge about IM injection application of students of nursing department of health sciences faculty of a university.METHODS: The universe of this study consisted of 395 students studying at the faculty of health sciences and the sample was composed of 200 students who were in school at the time of data collection and who agreed to participate in the post-informal study. The data of the study were collected by means of a questionnaire, which included questions about the introductory features and the IM injection process. Number and percentage distributions were used in the evaluation of the data.RESULTS: It was determined that 36.5% of the students who participated in the research were in the second grade, 59.5% of them were in the ages of 20-22, 48.5% of them were Anatolian - Science High School graduates and 64.0% were not willing to choose nursing profession. It was determined that 68.0% of the students changed the needle after preparing the medicine during the injection of IM, 58.0% used the air lock technique, 55.5% used the ventrogluteal region frequently when injecting IM, and 62.5% used Z approach when applying IM injection.DISCUSSION AND CONCLUSION: As a result of the study, it was determined that although the theoretical knowledge level of the students about intramuscular injection application is sufficient, they do not use evidence-based applications in practice.

GİRİŞ ve AMAÇ: Çalışma, bir üniversitenin sağlık bilimleri fakültesinde öğrenim gören hemşirelik bölümü öğrencilerinin IM enjeksiyon uygulaması ile ilgili bilgi düzeylerinin belirlenmesi amacıyla tanımlayıcı olarak yapılmıştır. YÖNTEM ve GEREÇLER: Araştırmanın evrenini sağlık bilimleri fakültesinde öğrenim görmekte olan 395 öğrenci, örneklemini ise verilerin toplandığı tarihlerde okulda bulunan ve bilgilendirme sonrası çalışmaya katılmayı kabul eden 200 öğrenci oluşturmuştur. Araştırmanın verileri, tanıtıcı özellikler ve IM enjeksiyon işlemine yönelik soruların yer aldığı anket formu ile toplanmıştır. Verilerin değerlendirilmesinde sayı ve yüzdelik dağılımları kullanılmıştır.BULGULAR: Araştırmaya katılan öğrencilerin % 36.5’inin ikinci sınıfta öğrenim görmekte, % 59.5’inin 20-22 yaşlarında, % 48.5’inin Anadolu – Fen Lisesi mezunu olduğu ve % 64.0’ünün hemşirelik mesleğini isteyerek seçmediği belirlenmiştir. Öğrencilerin % 68.0’inin IM enjeksiyon uygulaması esnasında, ilacı hazırladıktan sonra iğneyi değiştirdiği, % 58.0’inin hava kilidi tekniğini kullandığı, % 55.5’inin IM enjeksiyon uygularken sıklıkla ventrogluteal bölgeyi kullandığı, % 62.5’inin IM enjeksiyon uygularken Z yol tekniğini kullandığı saptanmıştır.TARTIŞMA ve SONUÇ: Bu araştırma sonucunda, öğrencilerin intramüsküler enjeksiyon uygulaması ile ilgili teorik bilgi düzeylerinin yeterli olmasına karşın, kanıta dayalı uygulamaları pratikte yeterli düzeyde kullanmadıkları belirlenmiştir.
Keywords: Knowledge level; Nursing students; Bilgi Düzeyi; Hemşirelik Öğrencileri; 4. Education